Pendidikan Perkoperasian Anggota Koperasi Syariah Al-Muhajir Bandung Guna Memahami Peran Koperasi Syariah Dalam Membangun Kesejahteraan Umat - Sobarna, Nanang; Agus Syaripudin, Muhammad; Rudiansyah, dkk, Rudiansyah (LPPM Universitas Koperasi Indonesia, 2024)
Sharia cooperatives are economic institutions that operate based on Islamic sharia principles, with the aim of improving the welfare of their members and the general public. One way to develop sharia cooperatives that are built through understanding the role of sharia cooperatives is through cooperative education, in order to understand administrators, managers and members in managing cooperatives in the right way to achieve common goals, namely improving the welfare of members and the community. This cooperative training aims to ensure that administrators, managers and members understand the role of sharia cooperatives in building the welfare of the people. The method used in cooperative education uses a lecture method followed by discussion and questions and answers accompanied by solutions. Through cooperative education, we are able to provide understanding to administrators, managers and members of the Al-Muhajir Bandung Sharia Cooperative as cooperative education participants that sharia cooperatives have a significant role in building the welfare of the people, through sharia economic principles in alleviating poverty, creating jobs, and improve social welfare